Meta-analysis of the effects of multi-component exercise on cognitive function in older adults with cognitive impairment - Liu, Hualei; Sun, Zhiyuan; Zeng, Haiqing; Han, Jincheng; Hu, Mengqi; Mao, Dewei; Tian, Xuewen; Li, Ran (Frontiers in Aging Neuroscience, 2025)
Exercise has been widely recognized as an effective regimen in mitigating cognitive decline. However, the effect of multi-component exercise (i.e., combination of two or more types of exercise) on cognitive function and its subdomains in older adults remains unclear. This meta-analysis aimed to explore the effects of multi-component exercise on cognitive functions in elderly individuals with cognitive impairment and identify optimal prevention and treatment strategies. A systematic search was conducted on PubMed, EBSCOhost, Web of Science, and Embase to identify relevant randomized controlled trials assessing the effect of multi-component exercise on cognitive function in the elderly. Thirteen studies with 1,776 participants were included in the analysis using Revman 5.4 software. The results showed that multi-component exercise had a significant effect on mitigating cognitive function decline in the elderly, with a pooled effect size of SMD = 0.31 (95% CI: 0.08, 0.55; p = 0.009). The results of subgroup analysis showed that interventions with ≥3 days/week, 12–24 weeks duration, and ≤ 40 min/session were significantly superior to other frequencies, durations, and lengths, with all p-values <0.05. Additionally, multi-component exercise had the most pronounced effects on executive function, visual memory, and verbal memory in patients with mild cognitive impairment (MCI). In conclusion, multi-component exercise can delay the decline in cognitive function in the elderly, and the intervention effects are modulated by various variables. Optimal intervention effects were observed with an exercise frequency of three or more times per week, a duration of 12 to 24 weeks, and a time per session of 40 min or less, particularly for improving executive function, visual memory, and verbal memory in patients with MCI.